2023
DOI: 10.3390/antibiotics12030530
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Insight into cfr-Mediated Linezolid-Resistant LA-MRSA in Italian Pig Holdings

Abstract: The cfr genes encode for a 23S rRNA methyltransferase, conferring a multiresistance phenotype to phenicol, lincosamide, oxazolidinone, pleuromutilin, and streptogramin A antibiotics. These genes have been described in staphylococci, including methicillin-resistant Staphylococcus aureus (MRSA). In this study, we retrospectively performed an in-depth genomic characterisation of three cfr-positive, multidrug-resistant (MDR) livestock-associated (LA) MRSA clonal complexes (CCs) 1 and 398 detected in different Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Similarly, Iurescia et al observed the presence of the cfr gene in three LA-MRSA isolated from Italian pig holdings using the WGS method. Among these isolates, two were susceptible to linezolid with an MIC of 1 µg ml −1 [34]. Another study from PR China by Sun et al detected 19 linezolid-resistant staphylococcal isolates from household animals.…”
Section: Lrsh Isolatesmentioning
confidence: 99%
“…Similarly, Iurescia et al observed the presence of the cfr gene in three LA-MRSA isolated from Italian pig holdings using the WGS method. Among these isolates, two were susceptible to linezolid with an MIC of 1 µg ml −1 [34]. Another study from PR China by Sun et al detected 19 linezolid-resistant staphylococcal isolates from household animals.…”
Section: Lrsh Isolatesmentioning
confidence: 99%